UNVEILING THE HISTORY AND ISLAMIC LAWS THROUGH THE TOMBSTONE OF SIRAJUDDIN ISA IN TUBAN, MAJAPAHIT - Arifia, Sariat; Mahdi, Mizuar; Muhammad, Taqiyuddin; Yaqin, Nurul; Alwi, M. Ali (International Journal of Social Service and Research, 2025)
This study explores the historical and religious significance of two Islamic tombstones from the Majapahit era in King King, Tuban, Java. The focus is on Sirajuddin Isa ibn Salahuddin Al Ma'bary's tombstone and an unnamed tombstone in the Mbah Randu complex. Through epigraphic and ornamental analysis, the research reconstructs the history of Islamic propagation in Java between the 13th and 15th centuries. Sirajuddin Isa is identified as a key figure in spreading Islam during the Majapahit period. His tombstone's inscriptions "Seek the Eternal", highlight the emphasis on monotheism and rejection of polytheism, suggesting early implementation of Islamic laws. While the Ornamental motifs like the lotus flower symbolize purity and spiritual enlightenment, blending local and Islamic traditions. The Hijri calendar's role in daily practices is also examined, indicating the integration of Islamic customs into Javanese life. These tombstones serve as historical artifacts illustrating the spread of Islam, the enforcement of Islamic laws, and cultural exchange between Islamic and local traditions in Java, highlighting Sirajuddin Isa's prominent role as an Islamic leader and legal authority during the Majapahit period.